An Innovative Approach to Design and Evaluate a Regional Coastal Ocean Observing System - Ostrander, Chris E.; Iwamoto, Melissa M.; Langenberger, Fiona (Frontiers in Marine Science, 2019)
Comprehensive and objective evaluation of all observing assets, tools, and services within an ocean observing system is essential to maximize effectiveness and efficiency; yet, it often eludes programs due to the complexity of such robust evaluation. In order to address this need, the Pacific Islands Ocean Observing System (PacIOOS) transformed an evaluation matrix developed for the energy sector to one suitable for ocean observing. The resulting innovation is a decision analysis methodology that factors in multiple attributes (market, risk, and performance factors) and allows for selective weighting of attributes based on system maturity, external forcing, and consumer demand. This evaluation process is coupled with an annual review of priorities with respect to stakeholder needs and the program’s five-year strategic framework in order to assess the system’s components. The results provide information needed to assess the effectiveness, efficiency, and impact of each component within the system, and informs a decision-making process that determines additional investment, refinement, sustainment, or retirement of individual observing assets, services, or component groups. Regularly evaluating, and taking action to improve, modify, or terminate weak system components allows for the continuous improvement of PacIOOS services by ensuring resources are directed to the priorities of the stakeholder community. The methodology described herein is presented as an innovative opportunity for others looking for a systematic approach to evaluate their observing systems to inform program-level decision-making as they develop, refine, and distribute data and information products.